STUDI KOMPARASI PENDAPATAN PEDAGANG PASAR KERATO SEBELUM DAN SETELAH RELOKASI (Studi Relokasi Pasar Seketeng Ke Pasar Kerato) - S Syafruddin; A Asmini; Opan Setia Pratama (Jurnal Ekonomi & Bisnis, 2020)
The purpose of this study was to analyze how relocation of market from Seketeng to Kerato affect vendors revenue. This type of research is a comparative study which aims to compare the vendors revenue before and after the relocation from Seketeng Market to Kerato Market. The type of data used in this research is quantitative data in the form of respondents' answers related to the research object obtained directly from the source through a questionnaire. The population in this study were all 669 vendors in Kerato Market. Sample are determined using the Slovin formula so that the sample selected represents the population as respondents which are 87 people. The data that had been collected were analyzed using the paired sample t- test analysis technique. The findings of this study indicate that the relocation of market from Seketeng to Kerato has an effect on vendors revenue. The average vendor income before relocating from Seketeng to Kerato was 92.00, while after relocation is 47.00. This means, after the relocation, the average vendors revenue decreased by 48.91%.